Mereka Memanggilku â€œKenthirâ€ - Sarwono, R Budi; Subandi, - (Faculty of Psychology, Universitas Gadjah Mada, 2013)
â€œKenthirâ€ is a stigma that commonly addressed to the psychosis sufferer in Javanese culture. This research studies about psychological dynamics of early phase of psychosis sufferer since they live in â€œkenthirâ€™sâ€ stigma and some other Javanese stigmas, and also about the influence of this stigma to their effort in doing re-integration with society in the context of Javanese culture. This qualitative research was conducted by the case study approach. The researcher was observed the psychological dynamics of four psychosis sufferers that was distributed in two regencies in Yogyakarta Special Region (Daerah Istimewa Yogyakarta). Beside this psychological dynamics, the thing that is observed by the researcher is how the psychosis sufferers attempt to re-integrate to the society. The primary research data is acquired both through systematic and unsystematic interview to the sufferer and the informant (family, neighbours, village officials, clinic psychologist, Mental Hospital psychologist and significant others). The supporting data is investigated from medically records data from Mental Hospital, doctorâ€™s prescription, status update from facebook account and other notes. The data are codified thematically grouped to be analyzed. The result shows that stigma in the Javanese society gave to the psychosis sufferers, is not always affect them during their reintegration in to the society. It solely depends on how each subject view that stigma. In fact, a patient publically called â€œkenthirâ€ by the surrounding people shows successful reintegration to the society. Keywords: kenthir, psikosis, reintegration, stigma